Nosocomial and community acquired infections in Korle Bu Teaching Hospital, Accra - Newman, M.J. (West African Journal Med. 28(5):300-3, 2010)
Nosocomial or hospital acquired infection has been recognized as a serious public health problem in the last twenty years. In most hospitals in Africa-South of the Sahara, although the types of community acquired infections are known, neither the magnitude, nor the common types of nosocomial infections has been documented.